2021
DOI: 10.3390/fluids6120450
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh–Bénard Instability of an Ellis Fluid Saturated Porous Channel with an Isoflux Boundary

Abstract: The onset of the thermal instability is investigated in a porous channel with plane parallel boundaries saturated by a non–Newtonian shear–thinning fluid and subject to a horizontal throughflow. The Ellis model is adopted to describe the fluid rheology. Both horizontal boundaries are assumed to be impermeable. A uniform heat flux is supplied through the lower boundary, while the upper boundary is kept at a uniform temperature. Such an asymmetric setup of the thermal boundary conditions is analysed via a numeri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The threshold conditions for the instability were obtained both theoretically and numerically and found that the instability sets in as oscillatory convection. Brandão et al (2021) extended the work of Celli et al (2021) by assuming a uniform heat flux at the lower boundary and a uniform temperature at the upper boundary. As a result, the stability eigenvalue problem is solved numerically and the destabilising effect of the Ellis fluid rheology is demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…The threshold conditions for the instability were obtained both theoretically and numerically and found that the instability sets in as oscillatory convection. Brandão et al (2021) extended the work of Celli et al (2021) by assuming a uniform heat flux at the lower boundary and a uniform temperature at the upper boundary. As a result, the stability eigenvalue problem is solved numerically and the destabilising effect of the Ellis fluid rheology is demonstrated.…”
Section: Introductionmentioning
confidence: 99%